MINAL `ILMI ILA AL-HADHARAH (THE URGENCY OF CHARACTER BUILDING IN ISLAMIC EDUCATION) - Moh. Tamtowi (Jurnal Penelitian Progresif, 2022)
Character building (character formation) is a basic goal in education. Character formation can be realized if the process of internalizing values ​​is successful. Values ​​that are lived and internalized in the soul will encourage the birth of new, innovative and dynamic creations. The essence of life is movement, the law of life is creation, so create a new, better world order of civilization. To build an advanced civilization, it is necessary to have a quality and forward-oriented education system. Education will be able to build an advanced mindset if the pattern of scientific development has an integralistic-encyclopedic pattern. The integralistic pattern necessitates continuous scientific dynamics in order to build an advanced civilization.